Prothrombin Fragment 1+2, Thrombin- Antithrombin III-Complexes and Fibrinopeptide A in Spontaneously Clotting Whole Blood In Vitro - Herren, Thomas; Werner Straub, P; Haeberli, André (Thrombosis and Haemostasis, 1994)
Previous in vitro studies using spontaneously clotting whole blood revealed thrombin formation and high fibrinopeptide A (FPA) concentrations measured during incubation time. This occurred in spite of normal concentrations of thrombin antagonists present in the blood of the healthy subjects examined. However, there are several reports showing that in vivo increased thrombin- anti thrombin III-complex (TAT) concentrations and relatively low FPA concentrations may occur e. g. in patients with (pre)thrombotic disorders. These in vivo findings indicate more effective thrombin inhibition by antithrombin III, with almost no fibrin formation. To find an explanation for the differences observed in vitro and in vivo, we extended the in vitro studies by measuring concentrations of prothrombin fragment 1 + 2 (F1 + 2), TAT and FPA at several time points until 30 min. Our goal was to test whether thrombin at least initially is neutralized by antithrombin III, resulting in a lack of fibrin formation, either in the absence or in the presence of heparin (0.2 and 0.5 U/ml whole blood, respectively).In the absence of heparin a simultaneous increase in the concentrations of F1+2, TAT and FPA was observed. Thrombin was only partially neutralized by antithrombin III and large amounts of fibrin were formed. The addition of heparin virtually suppressed thrombin formation since the F1 + 2 concentration remained low. Moreover, the small amounts of thrombin formed were neutralized by antithrombin III to a greater extent than in the absence of heparin. Thus, in the presence of heparin less fibrin was produced as evidenced by significantly lower FPA concentrations.Experiments using blood of two patients with antithrombin III deficiency showed that fibrin formation was not different from the healthy controls in spite of the significantly higher initial F1 + 2 concentration measured. During incubation, the patients tended to form more thrombin, of which proportionally less was neutralized by antithrombin III, and more fibrin as compared to the healthy controls. Heparin addition suppressed thrombin formation less efficiently.